The Effect of Project-Based Learning in the IPAS Project Subject on Students’ Employability Skills at State Vocational High School 1 Pasuruan - Taufik Hidayat; Tuwoso Tuwoso; Syaad Patmanthara (Didaktika: Jurnal Kependidikan, 2025)
This study investigates the effect of Project-Based Learning (PjBL) in the IPAS Project Subject on the employability skills of students at State Vocational High School 1 Pasuruan. The research was conducted to address the growing demand for vocational graduates who possess not only technical competencies but also essential employability skills such as communication, teamwork, problem-solving, critical thinking, adaptability, responsibility, and time management. A quasi-experimental one-group pre-test–post-test design was employed, involving 30 students selected through purposive sampling. Data were collected using an employability skills questionnaire, observation sheets, and a project assessment rubric. The results revealed a significant improvement in students’ employability skills after the implementation of PjBL. The mean pre-test score of 66.47, which indicated a moderate level of employability skills, increased to 82.63 in the post-test, placing students in the high category. Statistical analysis using a paired-sample t-test showed a significant difference between the pre-test and post-test scores (t = –14.872, p < 0.05), and the effect size calculation (Cohen’s d = 2.86) indicated a very large impact of the intervention. These findings demonstrate that Project-Based Learning is an effective pedagogical approach for enhancing employability skills in vocational education, particularly when integrated into interdisciplinary subjects such as IPAS within the Kurikulum Merdeka framework. Despite limitations related to the absence of a control group, the small sample size, and the short duration of implementation, this study provides empirical evidence supporting the integration of PjBL as a strategic method to strengthen students’ readiness for the world of work.